2004
DOI: 10.1007/s00127-004-0820-y
|View full text |Cite
|
Sign up to set email alerts
|

Community perception of mental disorders

Abstract: In Latin America and the Caribbean, there is a tendency to share the beliefs of the western medical model and few signs of the presence of elements from traditional medicine or religion. However, the studies exhibited various methodological gaps and problems. New studies, using more appropriate methodology, should be carried out in this region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(20 citation statements)
references
References 23 publications
0
18
2
Order By: Relevance
“…Salvadorans were less knowledgeable of biological bases, and had more misconceptions about and stigmas toward schizophrenics. This finding is not consistent with Toledo Piza and Blay (2004) who reported an overall positive attitude toward and identification of mental illnesses in Latin America. The recognition rate of schizophrenia found in E.S.…”
Section: Discussioncontrasting
confidence: 91%
See 2 more Smart Citations
“…Salvadorans were less knowledgeable of biological bases, and had more misconceptions about and stigmas toward schizophrenics. This finding is not consistent with Toledo Piza and Blay (2004) who reported an overall positive attitude toward and identification of mental illnesses in Latin America. The recognition rate of schizophrenia found in E.S.…”
Section: Discussioncontrasting
confidence: 91%
“…Generally, recognition of schizophrenia in a case vignette is high across countries, ranging from 70 to 90 percent (Angermeyer & Matschinger, 2003;Lauber, Nordt, Falcato, & Rössler, 2003;Link et al, 1999). Toledo Piza and Blay (2004) concluded that in Latin America, schizophrenia is the most identifiable mental illness, just as it is in developed countries (e.g., Brazil: D'Amorim, 1981; Dominica: Kohn, Sharma, Camilleri, & Levav, 2000;Mexico: Parra, 1987;Nicaragua: Penayo, Jacobsson, Caldera, & Bermann, 1988). In fact, they found that studies carried out in Latin America indicate a general positive attitude toward mental illnesses (e.g., Mexico: Garcia-Silberman, 1998; Argentina: Stefani, 1984).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…An overview of mental health research was conducted in 30 Latin American and Caribbean countries in order to understand the challenges in reducing the 10/90 gap 35. Most countries allocated less than 1% of their gross domestic product to research and human development, and less than 1% of their health budgets to mental health,11 with the consequence that mental health research publications from LAMICs comprise a small proportion of the world's total research output on mental health.…”
Section: Challenges Of Building Mental Health Research Capacity In Lamentioning
confidence: 99%
“…More important than lack of surveillance is the inadequacy of appropriate infrastructure and personnel trained in effective substance abuse disorder treatment guidelines (Dua et al, 2011). While health care services are often inadequate in developing countries, the gap between need and services is particularly great for mental health and substance user treatment, perhaps because of the stigma associated with these disorders (de Toledo Piza Peluso & Blay, 2004; Hugo, Boshoff, Traut, Zungu-Dirwayi, & Stein, 2003) where they are often considered moral failings, not diseases (Dickson-Gómez et al, 2010). The lack of attention to substance use disorders has disastrous effects for developing countries, including loss of productivity, high traffic fatalities, higher rates of crime, and HIV infection (De La Haye & Huidobro, 2010).…”
Section: Prefacementioning
confidence: 99%